Pengaruh Kinerja Lingkungan Terhadap Kinerja Keuangan Dengan Corporate Responsibility Sebagai Variabel Intervening Pada Perusahaan Manufaktur Yang Terdaftar Terdaftar Di Bursa Efek Indonesia Tahun 2015 – 2017 - Marini Yuniarti; Tapi Rumondang Sari Siregar (Universitas Negeri Medan (UNIMED), 2019)
Abstract : This research is about the problem of environmental performance on financial performance with corporate social responsibility as an intervening. This study aims to determine the Influence of Environmental Performance on Financial Performance with Corporate Social Responsibility as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange and participate in the Corporate Performance Assessment Program (PROPER) of the Ministry of Environment of the Republic of Indonesia. The research period used is 2015-2017. The population in this study are Manufacturing Companies listed on the Indonesia Stock Exchange and participate in the Corporate Performance Assessment Program (PROPER) of the Ministry of Environment of the Republic of Indonesia in the 2015-2017 observation period. The research sample was taken using a purposive sampling method . 24 Manufacturing Companies obtained as samples. The results of the first hypothesis analysis indicate that the results of the t test for environmental performance variables obtained a significance value of 0.096, which means greater than 0.05. While in the second hypothesis, the test results are seen from the significance value of the environmental performance variable of 0.001 which means less than 0.05. Furthermore, the third hypothesis is calculated by multiplying the indirect coefficient, namely ((0,051) x 13,236) = 0,675036 so that the total effect becomes (0,498 + (0,051) x 13,236)) = 1,173036. This means that the level of indirect influence of Environmental Performance on financial performance is 1,173036 greater than the direct relationship coefficient of 0,498. Based on the results of data analysis it can be concluded that: (1) Environmental Performance does not affect Financial Performance . (2) Environmental Performance has a positive and significant effect on Corporate Social Responsibility . (3) Partially Environmental Performance has a positive and significant effect on Financial Performance with Corporate Social Responsibility as an intervening variable. Keywords: environment performance, financial performance, corporate social responsibility